Decavanadate, decaniobate, tungstate and molybdate interactions with sarcoplasmic reticulum Ca2+-ATPase: quercetin prevents cysteine oxidation by vanadate but does not reverse ATPase inhibition - Fraqueza, Gil (2012)
Recently we demonstrated that the decavanadate (V10) ion is a stronger Ca2+-ATPase inhibitor than other oxometalates, such as the isoelectronic and isostructural decaniobate ion, and the tungstate and molybdate monomer ions, and that it binds to this protein with a 1 : 1 stoichiometry. The V10 interaction is not affected by any of the protein conformations that occur during the process of calcium translocation (i.e. E1, E1P, E2 and E2P) (Fraqueza et al., J. Inorg. Biochem., 2012). In the present study, we further explore this subject, and we can now show that the decaniobate ion, [Nb10 = Nb10O28]6−, is a useful tool in deducing the interaction and the non-competitive Ca2+-ATPase inhibition by the decavanadate ion [V10 = V10O28]6−. Moreover, decavanadate and vanadate induce protein cysteine oxidation whereas no effects were detected for the decaniobate, tungstate or molybdate ions. The presence of the antioxidant quercetin prevents cysteine oxidation, but not ATPase inhibition, by vanadate or decavanadate. Definitive V(IV) EPR spectra were observed for decavanadate in the presence of sarcoplasmic reticulum Ca2+- ATPase, indicating a vanadate reduction at some stage of the protein interaction. Raman spectroscopy clearly shows that the protein conformation changes that are induced by V10, Nb10 and vanadate are different from the ones induced by molybdate and tungstate monomer ions. Here, Mo and W cause changes similar to those by phosphate, yielding changes similar to the E1P protein conformation. The putative reduction of vanadium(V) to vanadium(IV) and the non-competitive binding of the V10 and Nb10 decametalates may explain the differences in the Raman spectra compared to those seen in the presence of molybdate or tungstate. Putting it all together, we suggest that the ability of V10 to inhibit the Ca2+- ATPase may be at least in part due to the process of vanadate reduction and associated protein cysteine oxidation. These results contribute to the understanding and application of these families of mono- and polyoxometalates as effective modulators of many biological processes, particularly those associated with calcium homeostasis.